Terrestrial Laser Scanning for Geometry-based Building Genealogy Research: Landshut, St. Martin’s and Two Transylvanian Saxon Churches - JOBBIK, Eszter (Studia Universitatis Babeș-Bolyai Historia Artium, 2024)
Terrestrial Laser Scanning for Geometry-based Building Genealogy Research: Landshut, St. Martin’s and Two Transylvanian Saxon Churches. Despite the abundance of literature on the construction and building methods of late Gothic net vaults, the most influential works still date back to the nineteenth and twentieth centuries. However, the use of terrestrial laser scanning enables researchers to gather precise geometric data that may challenge our current understanding of these vaults. This article presents a point-cloud-based geometric description of the nave vault in the St. Martin church of Landshut. This goes beyond the generally accepted literature on the topic of late Gothic net vaults. Based on the description, we categorise the vault into the geometric typologies of the net vaults’ rib-web connections and their rib systems’ global geometry, which we established during our earlier research. The literature has long discussed the guild connections between Landshut and the South-Transylvanian Saxon churches with masonry-ribbed vaults. Therefore, we present a comparative analysis of the St. Martin’s vaults and those in the naves of the churches in Mediaş (Medgyes/Mediasch) and Sighişoara (Segesvár/Schäßburg), two important examples of this group, based on the same geometric typologies we set up. Through our comparative analysis, we aim to address the question of how building genealogies should be approached. This section discusses the uncertain nature of deductions based solely on plan views of rib systems, how remnants from earlier building periods influence the construction method of net vaults, and the concept of centre and periphery in net vault construction.